Raising the Scores? : Empirical Evidence on the Introduction of the Three-Point Rule in Portugese Football - Ralf Dewenter (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
This paper provides an empirical analysis on the effectiveness of incentives when pay-offs were changed. Using data on Portuguese first division football matches the effects of the introduction of the so called three-point rule are analyzed applying panel count data techniques.
urn:nbn:de:gbv:705-opus-1591
Keywords: L8; C25; C23; L83; 330; Sports economics; Football; Incentives; Count data; Fußballsport; Professioneller Sport; Sportökonomik; Ökonomischer Anreiz; Schätzung; Portugal